2009
DOI: 10.1093/arclin/acp014
|View full text |Cite
|
Sign up to set email alerts
|

Executive Function and Decision-Making in Women with Fibromyalgia

Abstract: Patients with fibromyalgia (FM) typically report cognitive problems, and they state that these deficits are disturbing in everyday life. Despite these substantial subjective complaints by FM patients, very few studies have addressed objectively the effect of such aversive states on neuropsychological performance. In this study we aimed to examine possible impairment of executive function and decision-making in a sample of 36 women diagnosed with FM and 36 healthy women matched in age, education, and socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
174
5
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(211 citation statements)
references
References 32 publications
22
174
5
10
Order By: Relevance
“…Regarding EF, the patients showed impairment in the shifting subcomponent, which has already been highlighted by a previous study (38). Poor performances on complex tests that involve interference or attention switching have also been found in other chronic pain states (39).…”
Section: Discussionsupporting
confidence: 68%
“…Regarding EF, the patients showed impairment in the shifting subcomponent, which has already been highlighted by a previous study (38). Poor performances on complex tests that involve interference or attention switching have also been found in other chronic pain states (39).…”
Section: Discussionsupporting
confidence: 68%
“…Clinically, executive function is assessed using interference tasks such as the Wisconsin Card Sorting Test (Grant and Berg, 1948), the Process Dissociation Procedure (Jacoby, 1991), and flexibility tasks such as the Trail Making Test (Adjutant General's Office, 1944). Patient performances on these tests appear to show that controlled executive-type functions are affected by chronic pain (Karp et al, 2006;Ryan et al,1993;Verdejo-Garcia et al, 2009;Weiner et al, 2006), and may be more severely affected than less complex, automatic processes (for example fixed sequences of operations that do not require higher control) (Grisart and Van der Linden, 2001) (Table 1). Complex tests of attention, such as those that involve interference or attention switching, may require executive function and chronic pain patients perform poorly on such tests (Bosma and Kessels, 2002;Eccleston, 1994;Karp et al, 2006;Ryan et al, 1993).…”
Section: Executive Functionmentioning
confidence: 99%
“…However, this study did not include a pain-free control group and was carried out specifically in elderly pain patients (ages 84.6 ± 0.5 years). Emotional decision making and emotional self-regulation are also thought to involve higher executive functioning and appear to be compromised in some chronic pain patients (Apkarian et al, 2004a;Solberg Nes et al, 2009;Verdejo-Garcia et al, 2009). Interestingly, a study by Veldhuijzen et al (2006a) also found that chronic pain patients, while showing increased errors in an attentional task, had shorter response times than healthy controls.…”
Section: Executive Functionmentioning
confidence: 99%
See 2 more Smart Citations